Amrta - Akolakara, Gaṇeśa Vināyaka, 1909-; Śevāḷakara, Rāma, 1931-; Thatte, Yadunath Dattatray, 1922- (Māmā Kshīrasāgara Amrta Mahotsava Samitī ; prāptisthāna, Sādhanā Prakāśana, 1978)
Festschrift honoring Māmā Kshīrasāgara, b. 1903, educationist and social activist from Maharashtra; comprises articles contributed by educationists and social activists; includes an autobiographical account.